Orphan nuclear receptor ERRγ is a novel transcriptional regulator of IL-6 mediated hepatic BMP6 gene expression in mice - Radhakrishnan, Kamalakannan; Kim, Yong-Hoon; Jung, Yoon Seok; Kim, Jina; Kim, Don-Kyu; Cho, Sung Jin; Lee, In-Kyu; Dooley, Steven; Lee, Chul-Ho; Choi, Hueng-Sik (International journal of molecular sciences, 2020)
Bone morphogenetic protein 6 (BMP6) is a multifunctional growth factor involved in organ development and homeostasis. BMP6 controls expression of the liver hormone, hepcidin, and thereby plays a crucial role in regulating iron homeostasis. BMP6 gene transcriptional regulation in liver is largely unknown, but would be of great help to externally modulate iron load in pathologic conditions. Here, we describe a detailed molecular mechanism of hepatic BMP6 gene expression by an orphan nuclear receptor, estrogen-related receptor γ (ERRγ), in response to the pro-inflammatory cytokine interleukin 6 (IL-6). Recombinant IL-6 treatment increases hepatic ERRγ and BMP6 expression. Overexpression of ERRγ is sufficient to increase BMP6 gene expression in hepatocytes, suggesting that IL-6 is upstream of ERRγ. In line, knock-down of ERRγ in cell lines or a hepatocyte specific knock-out of ERRγ in mice significantly decreases IL-6 mediated BMP6 expression. Promoter studies show that ERRγ directly binds to the ERR response element (ERRE) in the mouse BMP6 gene promoter and positively regulates BMP6 gene transcription in IL-6 treatment conditions, which is further confirmed by ERRE mutated mBMP6-luciferase reporter assays. Finally, an inverse agonist of ERRγ, GSK5182, markedly inhibits IL-6 induced hepatic BMP6 expression in vitro and in vivo. Taken together, these results reveal a novel molecular mechanism on ERRγ mediated transcriptional regulation of hepatic BMP6 gene expression in response to IL-6.